Identifying serious underlying diagnoses among patients with brief resolved unexplained events (BRUEs): a Canadian cohort study - Sanjay Mahant; Nassr Nama; Ronik Kanani; Jessica Foulds; Julie Quet; Anupam Sehgal; Ran D Goldman; Jeffrey N Bone; Peter Gill; Martin Ogwuru; Parnian Hosseini; Zerlyn Lee; et al. (BMJ Paediatrics Open)
Objective To describe the demographics and clinical outcomes of infants with brief resolved unexplained events (BRUE).Design A retrospective cohort study.Setting 11 centres within the Canadian Paediatric Inpatient Research Network.Patients Patients presenting to the emergency department (ED) following a BRUE (2017–2021) were eligible, when no clinical cause identified after a thorough history and physical examination.Main outcome measures Serious underlying diagnosis (requiring prompt identification) and event recurrence (within 90 days).Results Of 1042 eligible patients, 665 were hospitalised (63.8%), with a median stay of 1.73 days. Diagnostic tests were performed on 855 patients (82.1%), and 440 (42.2%) received specialist consultations. In total, 977 patients (93.8%) were categorised as higher risk BRUE per the American Academy of Pediatrics guidelines. Most patients (n=551, 52.9%) lacked an explanatory diagnosis; however, serious underlying diagnoses were identified in 7.6% (n=79). Epilepsy/infantile spasms were the most common serious underlying diagnoses (2.0%, n=21). Gastro-oesophageal reflux was the most common non-serious underlying diagnosis identified in 268 otherwise healthy and thriving infants (25.7%). No instances of invasive bacterial infections, arrhythmias or metabolic disorders were found. Recurrent events were observed in 113 patients (10.8%) during the index visit, and 65 patients had a return to ED visit related to a recurrent event (6.2%). One death occurred within 90 days.Conclusions There is a low risk for a serious underlying diagnosis, where the majority of patients remain without a clear explanation. This study provides evidence-based risk for adverse outcomes, critical information to be used when engaging in shared decision-making with caregivers.